PENGARUH COMPETITION INTENSITY TERHADAP FIRM VALUE MELALUI EARNING MANAGEMENT SEBAGAI INTERVENING VARIABLE PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DALAM BURSA EFEK INDONESIA DI SURABAYA DAN DI SIDOARJO - Clarissa Claudia; Devie Devie (Business Accounting Review, 2016)
This study aimed to know significant direct affect of the competition intensity toward earning management, earning management toward firm value, and competition intensity toward firm value in manufacturing companies in Surabaya and Sidoarjo. Moreover, also to know significant indirect affect of competition intensity toward firm value through earning management in manufacturing companies in Surabaya and Sidoarjo. This study used quantitative method where the data were collected by distributing questionnaries to manufacturing companies in Surabaya and Sidoajo. The data collected were analyzed by using SmartPLS. The results of this study indicate that there was positive and signifikan relation of competition intensity toward earning management, negative and significant relation of earning management toward firm value and competition intensity toward firm value in manufacturing companies in Surabaya and Sidoarjo. But, earning management was inadequate to become as intervening variable between competition intensity and firm value. Because the direct relationship between competition intensity and firm value gave greater affect than if it was through earning management.